2014
DOI: 10.1371/journal.pgen.1004338
|View full text |Cite
|
Sign up to set email alerts
|

Ras-Mediated Deregulation of the Circadian Clock in Cancer

Abstract: Circadian rhythms are essential to the temporal regulation of molecular processes in living systems and as such to life itself. Deregulation of these rhythms leads to failures in biological processes and eventually to the manifestation of pathological phenotypes including cancer. To address the questions as to what are the elicitors of a disrupted clock in cancer, we applied a systems biology approach to correlate experimental, bioinformatics and modelling data from several cell line models for colorectal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
161
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(180 citation statements)
references
References 100 publications
19
161
0
Order By: Relevance
“…Because the circadian rhythm of hESCs could not be synchronized (data not shown; Yagita et al, 2010) and the heterogeneous composition of hEBs (Experimental Procedures) compromised interpretation, we turned to HCT116 cells. These cells display circadian gene expression (Reló gio et al, 2014) and significant amplitude in the oscillating transcription of a circadian chromatin hub of the 4C network, PARD3, upon serum shock ( Figures S4A and S4B). Given the role of CTCF and PARP1 in the interactions between LADs and circadian genes, we first examined CTCF-PARP1 proximities during the circadian cycle.…”
Section: Parp1 and Ctcf Regulate Circadian Transcription Bymentioning
confidence: 99%
“…Because the circadian rhythm of hESCs could not be synchronized (data not shown; Yagita et al, 2010) and the heterogeneous composition of hEBs (Experimental Procedures) compromised interpretation, we turned to HCT116 cells. These cells display circadian gene expression (Reló gio et al, 2014) and significant amplitude in the oscillating transcription of a circadian chromatin hub of the 4C network, PARD3, upon serum shock ( Figures S4A and S4B). Given the role of CTCF and PARP1 in the interactions between LADs and circadian genes, we first examined CTCF-PARP1 proximities during the circadian cycle.…”
Section: Parp1 and Ctcf Regulate Circadian Transcription Bymentioning
confidence: 99%
“…In mice, the dexamethasone-induced RAS protein 1 (DEXRAS1) is suggested to be an input factor of the circadian clock (49)(50)(51)(52). Both experimental data and bioinformatic analysis suggest that oncogenic RAS proteins are involved in the deregulation of the circadian clock in cancer cells (53). Finally, it was recently shown that RASsignaling affects the circadian clock in the suprachiasmatic nucleus of mice acting, at least partially, via ERK and glycogen synthase kinase (GSK), and thereby fine-tunes the circadian period (54).…”
Section: Introductionmentioning
confidence: 99%
“…In a series of researchers was revealed the presence of circadian rhythms at obstruction of respiratory tracts at pulmonary chronic obstructive diseases [14] and especially asthma [15]. It conditions the necessity of wide introduction of chronotherapy methods in COPD treatment schemes.…”
Section: Medicine and Dentistrymentioning
confidence: 99%